Effects of Particle Diameter and Permeability on Air Cooling Performance of a Porous Bed (Applied Research and Innovation, 2025)
This study investigates varying particle diameters and porosity to improve the cooling performance of a porous bed. It also considers actual and scaled-down clinker bed sizes. The result from the study was validated with existing data from actual-size clinker beds. For the actual size, predicted air outlet temperature, when compared to the experimental and numerical simulation results produced deviation of –5.46% and +1.65% respectively. For the scaled down-sizes, the air outlet temperature when compared with the actual size of experimental result, yielded deviations of 3.96% and 4.9% because the scaled sizes have 3 and 9 scale factors, respectively. The initial increase in air outlet temperature was minimal, but as the diameter increased, the temperature reduction became significant. The rate of air outlet temperature decrease was slightly consistent from 0.1 to 0.5, but widens as porosity increases. However, as porosity increases, the rate widens. Furthermore, it was discovered that, the heat transfer rate between air and clinker decreases less significantly between diameters of 0.01 to 0.02 m, but increases as porosity increases to 0.6, 0.7, and 0.8, resulting in a significant reduction. The study concluded that as clinker particle diameter increases, outlet temperature also increases, pressure drop decreases, with a significant decrease observed between 0.01 and 0.02 m and porous bed with scale factor 9 had high pressure drop values as the other three bed sizes showed similar results.